Manajeman Syok Hipovolemia pada Pasien Plasenta Akreta dengan Tindakan Caesarean Hysterectomy di Kamar Operasi - Erna Nurhasanah; Christantie Effendy; Abror Shodiq; Elsi Dwi Hapsari (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2025)
Latar Belakang: Plasenta akreta merupakan komplikasi obstetrik yang jarang, tetapi sangat berisiko karena berpotensi menimbulkan perdarahan masif intraoperatif yang dapat meningkatkan angka morbiditas dan mortalitas. Oleh sebab itu, penanganan syok hipovolemia sangat penting untuk mempertahankan kestabilan hemodinamik dan mendukung hasil pembedahan yang optimal. Laporan ini membahas penanganan syok hipovolemia pada pasien plasenta akreta yang menjalani operasi caesarean hysterectomy/histerektomi sesar. Keluhan Utama Pasien:  Pasien perempuan usia 27 tahun mengalami perdarahan 4.000 ml selama histerektomi sesar hingga mengalami syok hipovolemik. Tindakan keperawatan meliputi pemasangan tiga IV-line besar (16G, 14G, 18G), pemasangan kateter, resusitasi cairan, dan transfusi 7 PRC, 5 FFP, 5 TC, pemberian norepinefrin dan asam traneksamat. Hasil: Setelah perdarahan masif berhasil diatasi, total cairan yang masuk dan keluar selama prosedur operasi dihitung untuk mengevaluasi efektivitas terapi cairan yang diberikan. Total cairan masuk 6.750 ml, cairan keluar 6.352 ml, dengan keseimbangan +398 ml. Monitoring hemodinamik dilakukan ketat, urine output 0,877 ml/kg/jam. Kesimpulan: Manajemen cairan terintegrasi dengan pemantauan intensif dan kolaborasi tim sangat penting untuk menghindari komplikasi syok dan disfungsi organ.Kata Kunci: cairan intraoperatif, perdarahan masif, plasenta akreta, syok hipovolemiaABSTRACTBackground: Placenta accreta is a rare but high-risk obstetric condition due to the potential for massive intraoperative hemorrhage, which can significantly increase maternal morbidity and mortality. Effective management of hypovolemic shock is essential to maintain hemodynamic stability and ensure optimal surgical outcomes. This case report discusses the management of hypovolemic shock in a patient with placenta accreta undergoing cesarean hysterectomy. Methods: This case report describes intraoperative fluid management in a patient with placenta accreta who experienced massive hemorrhage during surgery. The data include the type and volume of fluids administered—crystalloids, colloids, and blood components—as well as total fluid output during the procedure. Results: A 27-year-old female experienced 4,000 ml of blood loss during cesarean hysterectomy, resulting in hypovolemic shock. Nursing interventions included insertion of three large-bore IV lines (16G, 14G, 18G), urinary catheterization, fluid resuscitation, and administration of 7 PRC, 5 FFP, 5 TC, norepinephrine, and tranexamic acid. Total fluid intake was 6,750 ml (2,300 ml blood components, 3,200 ml crystalloids, 1,250 ml colloids), with an output of 6,352 ml and a positive balance of +398 ml. Hemodynamic parameters were closely monitored using invasive arterial pressure monitoring. Urine output reached 0.877 ml/kg/hr, indicating preserved renal function despite severe physiological stress. Conclusion: Intraoperative fluid management in placenta accreta requires a well-coordinated approach combining crystalloids, colloids, and blood components. Intensive monitoring and multidisciplinary collaboration are crucial to prevent complications such as hypovolemic shock and organ failure.Keywords: placenta accreta, hypovolemic shock management, massive hemorrhage, intraoperative fluid therapy